(untitled) (Práxis Educativa, 2022)
In this text, it is sought to describe and analyze the political dimension of the November 20th celebration held in the Quilombola community of Campina de Pedra, Poconé, Mato Grosso (MT), Brazil, and understand how the school dialogues with all the black symbology that permeates it. Methodologically, it is based on ethnography. Observations and interviews with some celebrators and schoolteachers were conducted. Ethnographic writings are the result of the experiences they had during the XI Quilombola Encounter held in November 2015, recorded in the field notebook. Theoretically, it is based on Castro Júnior (2014), Pessoa (2005), Ribeiro Júnior (1982), among others. The results point out that the Quilombola celebration is a privileged space of revindications, memory, history, and knowledge that are manifested in/around the body. The school demonstrates some shyness to establish a pedagogical intercommunication with the celebration. It is understood that the festive moments collaborate with strengthening and identity statements, as the elements of the past and present manifested in the festive body relate. Therefore, they do not match the epistemic logic of modernity and coloniality and, thus, are conducive elements for a contextualized education to the historical, social and cultural universe of Quilombos. Keywords: Education. Quilombo. Quilombola Celebration.